1997
DOI: 10.1080/135457097338799
|View full text |Cite
|
Sign up to set email alerts
|

''Bargaining'' and Gender Relations: Within and Beyond the Household

Abstract: Highlighting the problems posed by a ''unitary'' conceptualization of the household, a number of economists have in recent years proposed alternative models. These models, especially those embodying the bargaining approach, provide a useful framework for analyzing gender relations and throwing some light on how gender asymmetries are constructed and contested. At the same time, the models have paid inadequate or no attention to some critical aspects of intra-household gender dynamics, such as: What factors (es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

30
922
0
44

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 1,209 publications
(996 citation statements)
references
References 35 publications
30
922
0
44
Order By: Relevance
“…Moreover, these traditional kinship institutions play a major role in determining the bargaining power of women, which in turn affect the health and economic welfare of women and female children of developing countries such as India (Agarwal 1994(Agarwal , 1997Folbre 1997;Miller 1981).…”
Section: Kinship Institutions and Female Bargaining Powermentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, these traditional kinship institutions play a major role in determining the bargaining power of women, which in turn affect the health and economic welfare of women and female children of developing countries such as India (Agarwal 1994(Agarwal , 1997Folbre 1997;Miller 1981).…”
Section: Kinship Institutions and Female Bargaining Powermentioning
confidence: 99%
“…Because women marry into familiar kin networks rather than to strange families, they are likely to have more allies. Women's property rights are positively correlated with marriages in which women are in close proximity to their natal home, which is often the case in cross-cousin marriages (Agarwal 1994). While the underlying causes of cross-cousin marriages are complex, Agarwal (1994) has argued that cross-cousin marriages were an important means of keeping landed property within kin groups even if inheritance was matrilineal (ancestral property passes through the female line) or bilateral (ancestral property passes through both females and males).…”
Section: Kinship Institutions and Female Bargaining Powermentioning
confidence: 99%
See 2 more Smart Citations
“…Studies in the US have found that abused women who were employed were more likely to initiate divorce proceedings, go to the police or leave the relationship [9,13,21]. The emphasis on employment as the route out of abuse is, however, argued to be simplistic and culture and context are said to determine women’s ability to act on their behalf [22–26]. Instead, studies in low- and middle-income countries (LMIC) have found education, rather than employment, to be the empowering resource enabling women to separate [11,14,25].…”
Section: Introductionmentioning
confidence: 99%